Divergent synthesis of chiral cyclic azides via asymmetric cycloaddition reactions of vinyl azides - Nuligonda Thirupathi (Nature Portfolio, 2019)
Vinyl azides generally act as 3-atom synthon through the fast release of molecular nitrogen, whereas keeping the azide group intact is more challenging. Here, the authors show a copper-catalyzed enantioselective cycloaddition of two types of vinyl azides generating a diverse pool of valuable chiral cyclic azides.